SAT0291 Serum Osteopontin in GIANT Cell Arteritis: Abiomarker Associated with Systemic Inflammatory Response and Relapsing Course. (10th June 2014) - Prieto-González, S.; Corbera-Bellalta, M.; Planas-Rigol, E.; García-Martínez, A.; Alba, M.A.; Tavera-Bahillo, I.; Espígol-Frigolé, G.; Murgia, G.; Hernández-Rodríguez, J.; Cid, M.C.
Abstract : Background: Osteopontin (OPN) is a multifunctional glycoprotein with a relevant role in inflammatory scenarios, contributing to macrophage chemotaxis as well as Th1 and Th17 differentiation. Potential role of OPN in giant cell arteritis (GCA) pathogenesis has not been explored to date. Objectives: The aim of our study was to determine OPN concentration in sera from GCA patients and its relationship with disease activity and persistence. Methods: OPN levels in serum from 76 GCA patients at the time of diagnosis and from 25 healthy controls were measured by ELISA (R&D Systems). A second measure was performed in 36 patients of the series in remission, after one year of GC treatment. Clinical manifestations and laboratory findings at diagnosis, and data about treatment requirements and relapses during follow-up were recorded. Results: Serum OPN concentrations were significantly elevated in active patients (104, 76±65, 02) compared with healthy controls (41, 29±22, 67, p<0, 001) or patients in remission (48, 78±23, 97; p<0, 001). Patients with systemic symptoms presented OPN levels significantly higher at diagnosis (107, 15±55, 03 vs 64, 13±37, 35; p<0, 001). Circulating OPN showed a positive correlation with ERS, CRP (both r=0, 35; p=0, 006) and IL-6 (r=0, 52; p<0, 001). Relapsing patients presented baseline OPN concentrations significantly higher than patients who achieved sustained remission (129, 00±71, 81 vs 81, 62±42, 15; p=0, 02), and longer time to achieve a stable daily steroid dose <10 mg and 5 mg (r=0, 37, p=0, 02 and r=0, 45, p=0, 03, respectively). Cumulated prednisone dosage at withdrawal correlated with baseline circulating OPN concentrations (r=0, 40, p=0, 01). Conclusions: Increased serum OPN levels are found in active GCA patients at diagnosis and correlate with the intensity of the systemic inflammatory response and treatment requirements. OPN may have a relevant role as a proinflammatory biomarker and may be related to the persistence of inflammatory activity in GCA.Supported by SAF 11/30073. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5597